THE IMPACT OF MODERN TECHNOLOGIES ON EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Human can not envision his life without advanced innovations. The impacts of advances can be seen in each circle. It can allow full data approximately cutting edge innovation devices in instructive range. Different online stages make beneficial impacts in working and considering circle. Moodle, Wikipedia, Google Researcher are one sorts of these stages. In any case, in this thing has too negative destinations and this article edified the complete.